Attachment style as a mediator between childhood maltreatment and the experience of betrayal trauma as an adult. (February 2016) - Hocking, Elise C.; Simons, Raluca M.; Surette, Renata J.
Abstract: Previous research has demonstrated a positive association between child maltreatment and adult interpersonal trauma (Arata, 2000; Crawford & Wright, 2007 ). From a betrayal trauma theory perspective, evidence suggests that the experience of trauma high in betrayal (e.g., child maltreatment by parents or guardians) increases ones risk of betrayal trauma as an adult (Gobin & Freyd, 2009 ). However, the mechanisms explaining these associations are not well understood; attachment theory could provide further insight. Child maltreatment is associated with insecure attachment (Baer & Martinez, 2006; Muller et al., 2000 ). Insecure attachment is also associated with deficits in interpersonal functioning and risk for intimate partner violence, suggesting insecure attachment may mediate the relationship between child maltreatment and the experience of betrayal trauma as an adult. The current study tested this hypothesis in a sample of 601 college students. Participants completed online questionnaires including the Child Abuse and Trauma Scale (CATS), the Experiences in Close Relationships – Revised (ECR-R) and the Brief Betrayal Trauma Survey (BBTS). Results indicated that child maltreatment is associated with adult betrayal trauma and anxious attachment partially mediates this relationship.